Keystream encryption device, method, and program (2007)
A stream encryption device generates a first pseudo random number sequence from key information, generates a second pseudo random number sequence according to clock control performed according to the first pseudo random number sequence, and subjects it to a nonlinear function calculation, thereby generating a key stream. The stream encryption device performs XOR operation with a plain text so as to create an encrypted text.